Linking sustainable business models and supply chains — Toward an integrated value creation framework - Simon Norris; Julia Hagenbeck; Stefan Schaltegger (Business Strategy and the Environment, 2021)
Extant literature on sustainable business models highlights that value creation stems from resources exchanged in relationships between a focal firm and its stakeholders. In this context, the literature has, so far, focused on direct relationships. However, despite the acknowledged relevance of sustainability issues in supply chains, this relational view of the focal company and its direct stakeholders has not been extended toward value creation for and with indirect stakeholders, such as stakeholders of suppliers. Addressing this gap, this conceptual article integrates a relational view of sustainable supply chain management into the management of sustainable business models. It extends the scope of sustainable business models from relationships between the focal firm and its direct stakeholders to indirect relationships with stakeholders of suppliers. A framework is developed that supports analysis and management of value-creating relationships between the focal firm, suppliers, and stakeholders of suppliers. By extending the conceptualization of sustainable business models to consider relationship chains beyond direct relationships, this article proposes that a focal firm has to actively manage interactions both with suppliers and with suppliers' stakeholders.
Keywords: 330; business model; corporate sustainability; integrated framework; multi-tier supply chain; relational view; stakeholders; sustainable supply chain management; value creation